An Analysis Of Ethical And Legal Issues In Organ Transplantation And Organ Donation In Indonesia - Kadek Dwi Pradnya Lestari; I Gusti Agung Gede Utara Hartawan (Jurnal Smart Hukum (JSH), 2026)
The development of modern medical science has brought significant advancements in efforts to save human lives, one of which is through organ transplantation. Although organ transplantation offers significant benefits to the medical field, it also raises various complex issues that encompass ethical, legal, social, and religious dimensions. This study utilizes a qualitative descriptive method and a library research approach to explore the legal framework and bioethical principles that govern organ transplantation in Indonesia. The analysis reveals that the legal regulations concerning organ transplantation in Indonesia have undergone substantial development. Law Number 17 of 2023 on Health stipulates that organ transplantation may only be conducted for humanitarian purposes and explicitly prohibits any form of organ commercialization. Furthermore, Government Regulation Number 28 of 2024 provide the technical foundation related to the procedures, hospital licensing, and the establishment of transplantation ethics committees. From an ethical standpoint, organ transplantation practices must adhere to the four fundamental principles of bioethics, beneficence, autonomy, non-maleficence, and justice which position patients as autonomous subjects in medical decision-making. Religious factors also have a major effect on public perception: Catholicism and Islam regard organ donation as an act of charity and solidarity, Hinduism associates it with the concept of dāna (sacred giving); while Buddhism views it as a noble expression of compassion. Therefore, the implementation of organ transplantation in Indonesia must be carried out within a robust legal and ethical framework, harmonized with the prevailing humanitarian and spiritual values of the society. Keyword: organ transplantation, Bioethics, Health Law, Organ Donation, Religious Values.